Implementation of Round Robin Algorithm in Public Transportation Scheduling System at Pakupatan Terminal in Serang City-Indonesia - Darip, Mochammad (ISB Atma Luhur, 2025)
Public transportation scheduling, particularly for city transit systems, is a critical factor in improving service efficiency and passenger comfort. The main issues commonly encountered include irregular schedules and long passenger waiting times. This study aims to implement the Round Robin algorithm for scheduling angkot (public minivans) at Pakupatan Terminal. The Round Robin algorithm was selected due to its ability to allocate time evenly among vehicles, thereby reducing waiting times and increasing departure frequency. The methodology involves collecting data on the number of angkot in operation, their working hours, and passenger demand patterns at Pakupatan Terminal. The Round Robin algorithm is then applied to generate departure schedules based on predefined time intervals. The implementation results demonstrate improved scheduling efficiency, with passenger waiting times reduced by up to 10 minutes and user satisfaction increased by 25%. Further analysis evaluates the impact of the algorithm on traffic flow and passenger density at the terminal. The findings are expected to assist public transportation managers in developing more effective scheduling systems—particularly at Pakupatan Terminal in Serang City—and to serve as a reference for future research in transportation systems. Thus, the implementation of the Round Robin algorithm can be considered an effective solution for enhancing angkot services in the area.